Exploring climate change resilience of major crops in Somalia: implications for ensuring food security - Abdikafi Hassan Abdi; Mohamed Okash Sugow; Dhaqane Roble Halane (International Journal of Agricultural Sustainability)
The complex relationship between climate change and major crop output poses urgent challenges for contemporary food production systems. Recognizing the diverse responses of different crops to climatic stressors, it is necessary to investigate the repercussions of climate-induced shifts in various crop yields. Focused on the adverse extreme weather impacts on food security, this research employs multiple specifications to assess the effects of climate change on major crops—maize, sorghum, rice, wheat, sugarcane, bananas, and beans—in Somalia using annual data spanning 1991–2019. The empirical findings from the autoregressive distributed lag (ARDL) approach reveal that increasing precipitation positively impacts the long-run output of sorghum, sugarcane, and banana while adversely affecting bean production. Conversely, changing temperatures detrimentally affect the long-run output of sorghum, rice, and beans, although they enhance rice and sorghum production in the short-run. Intriguingly, the study reveals that greenhouse gas (GHG) emissions and crop-harvested areas significantly enhance the yields of various crops. Moreover, agricultural labour positively impacts bananas while hampering other crop outputs. Based on these results, the study proposes the adoption of climate-resilient crop varieties, investment in irrigation infrastructure, enhanced weather prediction and early warning systems, as well as the promotion of sustainable land management.